Hedgehog signalling stimulates precursor cell accumulation and impairs epithelial maturation in the murine oesophagus. Issue 3 (13th April 2012) - van Dop, Willemijn A; Rosekrans, Sanne L; Uhmann, Anja; Jaks, Viljar; Offerhaus, G Johan A; van den Bergh Weerman, Marius A; Kasper, Maria; Heijmans, Jarom; Hardwick, James C H; Verspaget, Hein W; Hommes, Daan W; Toftgård, Rune; et al.
Abstract : Objective: In the intestine Hedgehog (Hh) signalling is directed from epithelium to mesenchyme and negatively regulates epithelial precursor cell fate. The role of Hh signalling in the oesophagus has not been studied in vivo. Here the authors examined the role of Hh signalling in epithelial homeostasis of oesophagus. Design: The authors used transgenic mice in which the Hh receptor Patched1 ( Ptch1 ) could be conditionally inactivated in a body-wide manner and mice in which Gli1 could be induced specifically in the epithelium of the skin and oesophagus. Effects on epithelial homeostasis of the oesophagus were examined using immunohistochemistry, in situ hybridisation, transmission electron microscopy and real-time PCR. Hh signalling was examined in patients with oesophageal squamous cell carcinoma (SCC) by quantitative real-time PCR. Results: Sonic Hh is signalled in an autocrine manner in the basal layer of the oesophagus. Activation of Hh signalling resulted in an expansion of the epithelial precursor cell compartment and failure of epithelial maturation and migration. Levels of Hh targets GLI1, HHIP and PTCH1 were increased in SCC compared with normal tissue from the same patients. Conclusion: Here the authors find that Hh signalling positively regulates the precursor cell compartment in the oesophageal epithelium in an autocrine manner. Since Hh signalling targets precursor cells in the oesophageal epithelium and signalling is increased in SCCs, Hh signalling may be involved in oesophageal SCC formation.